2019
DOI: 10.3390/molecules24183244
|View full text |Cite
|
Sign up to set email alerts
|

A Secreted Phospholipase A2 Induces Formation of Smooth Muscle Foam Cells Which Transdifferentiate to Macrophage-Like State

Abstract: Vascular smooth muscle cells (VSMCs) loaded with lipid droplets (LDs) are markers of atherosclerosis. In this disease, inflammatory Group IIA-secreted phospholipase A2s (GIIA sPLA2s) are highly expressed in VSMCs, but their actions in these cells are unknown. Here, we investigated the ability of myotoxin III (MT-III), an ophidian GIIA sPLA2 sharing structural and functional features with mammalian GIIA sPLA2s, to induce LD formation and lipid metabolism factors involved in this effect. Modulation of VSMC pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
1
10
1
1
Order By: Relevance
“…In line with the ability of svPLA 2 s to elicit an inflammatory response characterized by a high level of inflammatory mediators and free fatty acids, it was demonstrated that MT-III (Asp49 PLA 2 ), isolated from B. asper venom, induced LD formation enriched by PLIN2 protein in mice peritoneal macrophages [170]. This effect was likewise observed in rat vascular smooth muscle cells isolated from the thoracic aorta stimulated by MT-III [168]. Moreover, the ability of MT-II, a Lys49 PLA 2 homologue devoid of catalytic activity from B. asper venom, to directly activate macrophages to form LDs was reported [167].…”
Section: Bothrops Svpla 2s Trigger Lipid Accumulation In Immunocompetent Cellsmentioning
confidence: 68%
“…In line with the ability of svPLA 2 s to elicit an inflammatory response characterized by a high level of inflammatory mediators and free fatty acids, it was demonstrated that MT-III (Asp49 PLA 2 ), isolated from B. asper venom, induced LD formation enriched by PLIN2 protein in mice peritoneal macrophages [170]. This effect was likewise observed in rat vascular smooth muscle cells isolated from the thoracic aorta stimulated by MT-III [168]. Moreover, the ability of MT-II, a Lys49 PLA 2 homologue devoid of catalytic activity from B. asper venom, to directly activate macrophages to form LDs was reported [167].…”
Section: Bothrops Svpla 2s Trigger Lipid Accumulation In Immunocompetent Cellsmentioning
confidence: 68%
“…It has been confirmed that, in macrophages, PPAR-γ and LXR-α controlled the cholesterol removal through the modulation of ABCA1 [ 25 ]. Karina and colleagues revealed that, myotoxin III (an ophidian GIIA sPLA2) increased PPAR-γ and ABCA1 expression, and was involved in the lipid metabolism [ 28 ]. Consistently, our results indicated that sPLA2-IIA might increase the expression of ABCA1 through PPAR-γ/LXR-α pathway in THP-1 cells, and subsequently augment the cholesterol efflux capacity of cells.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Accordingly, targeting ClC-3 could be employed as a potential therapeutic strategy for AS, at least in part, by regulating JNK/p38 MAPK-dependent SRa expression and foam cell formation (Figure 3). 77…”
Section: Clc-3 and Macrophage Pro-inflammatory Activationmentioning
confidence: 99%